1995
DOI: 10.1164/ajrccm.152.1.7599827
|View full text |Cite
|
Sign up to set email alerts
|

The Breuer-Hering reflex in humans. Effects of pulmonary denervation and hypocapnia.

Abstract: Passive lung inflation in humans causes reflex expiratory prolongation that is abolished by vagal blockade. We have studied two aspects of this classic Breuer-Hering reflex in humans: the effect of pulmonary denervation from bilateral lung transplantation, and the effect of alveolar hypocapnia. Lung inflations were performed in six normal subjects and four lung transplant patients during triazolam-induced sleep using a negative pressure body box. Lung inflation with isocapnic gas in normal subjects resulted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
1
2

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 21 publications
5
48
1
2
Order By: Relevance
“…These are large diameter myelinated fibers with a fast conduction velocity and a low electrical threshold; they are present in all mammals so far tested; and have been recorded directly from the human vagus [17]. Moreover, experiments in conscious human volunteers have shown the presence of a Hering-Breuer reflex that is dependent on innervation of the lungs [18]. Although the reflex in humans has a higher threshold than that seen typically in experimental animals [19], we expect that 50 Hz stimulation of this whole afferent population should comfortably exceed that threshold.…”
Section: Discussionmentioning
confidence: 99%
“…These are large diameter myelinated fibers with a fast conduction velocity and a low electrical threshold; they are present in all mammals so far tested; and have been recorded directly from the human vagus [17]. Moreover, experiments in conscious human volunteers have shown the presence of a Hering-Breuer reflex that is dependent on innervation of the lungs [18]. Although the reflex in humans has a higher threshold than that seen typically in experimental animals [19], we expect that 50 Hz stimulation of this whole afferent population should comfortably exceed that threshold.…”
Section: Discussionmentioning
confidence: 99%
“…prior to 12 months post-transplantation (Higenbottam et al 1989;Hathaway et al 1993;Iber et al 1995;cf. Ramaekers et al 1996), pulmonary reinnervation has been reported after about 8 months in allograft transplanted rats (Kawaguchi et al 1998), 5 months in autotransplanted dogs (Mattila et al 1987) and 2 months in autotransplanted monkeys (Mihm et al 1989).…”
Section: Discussionmentioning
confidence: 99%
“…The majority (7 out of 8) of these subjects had been transplant recipients in the previous 13 months or less so the chance of reinnervation of the lungs was considered to be small (Higenbottam et al 1989;Hathaway et al 1993;Seals et al 1993;Iber et al 1995;Ramaekers et al 1996). All transplant subjects were clinically well at the time of the study but were on a regimen of immunosuppression and antimicrobial medications.…”
Section: Methodsmentioning
confidence: 99%
“…This prolongation of tI/ttot and fR was dose-dependent and instantaneous, suggesting that upper airway and pulmonary mechanoreceptors, rather than chemoreceptors, mediated these immediate responses to UAO [28][29][30][31][32][33]. The increase in tI/ttot should help to stabilise V9E at any given level of UAO, as described by the following equation [17,18,20], which was imposed experimentally.…”
Section: Timing Responses To Uaomentioning
confidence: 99%